Rhodium(iii) catalyzed olefination and deuteration of tetrahydrocarbazole. Issue 14 (23rd February 2021) - Peng, Wan; Liu, Qiaohong; Yin, Fucheng; Shi, Cunjian; Ji, Limei; Qu, Lailiang; Wang, Cheng; Luo, Heng; Kong, Lingyi; Wang, Xiaobing
Abstract : The rhodium-catalyzed olefination and deuteration of tetrahydrocarbazoles in water with the aid of an N, N -dimethylcarbamoyl-protected group is presented. Abstract : The rhodium-catalyzed olefination and deuteration of tetrahydrocarbazoles in water with the aid of an N, N -dimethylcarbamoyl-protected group is presented. This olefination method features a broad substrate scope, good functional-group tolerance, and high efficiency in water. Practical applications of the protocol are illustrated by the synthesis of various evodiamine derivatives. As such, this environmentally friendly approach to directly modify natural products will attract much attention in academic and industrial research.